Antagonistic potential of Trichoderma harzianum and Purpureocillium lilacinum on Ceratocystis fimbriata in soil cultivated with eucalyptus - Antonio, Gabriel Leonardi [UNESP]; Firmino, Ana Carolina [UNESP] (FapUNIFESP (SciELO), 2024)
Cultivation of eucalyptus is of great importance in Brazil. Ceratocystis wilt is a disease of great economic relevance in the country, affecting eucalyptus, cacao and mango crops. New alternatives are needed for the management of this disease because infected plants frequently have to be removed from the area, causing losses to the farmers. The present study aimed to evaluate the efficiency of biological control agents (Trichoderma harzianum and Purpureocillium lilacinum), applied by different modes, against Ceratocystis fimbriata in the soil. The experiment was conducted in a greenhouse in Dracena – São Paulo State, in two phases: one phase of 4 months with 90-day-old seedlings, and another phase of 2 months with 60-day-old seedlings. The following treatments were performed: Infested soil and soaking (IS + S); Infested soil and hydrogel (IS + H); Infested soil and irrigation (IS + IR); Infested soil and powder (IS + P); Negative Control (NC); Positive Control (CP). Results indicated that plants inoculated with the pathogen and treated with the control agents tended to have a higher chlorophyll index. Treatments with both biological agents applied by irrigation and powder in the soil (IS+IR and IS+P) presented the best and most consistent results for the two tested seedling ages.
Potencial Antagônico de Trichoderma harzianum e Purpureocillium lilacinum contra Ceratocystis fimbriata em solo cultivado com eucalipto
Keywords: antagonistic fungi; biological control; wilt